Translation, cross-cultural adaptation and validation of the vitiligo-specific health-related quality of life instrument (VitiQoL) into Brazilian Portuguese - Boza, Juliana Catucci (An Bras Dermatol, 2015)
BACKGROUND: Vitiligo, although asymptomatic, highly compromises patients' quality of life (QoL). Therefore, an adequate evaluation of QoL is essential. OBJECTIVES: Translation, cultural adaptation and validation of VitiQol (Vitiligo-specific health-related quality of life instrument) into Brazilian Portuguese. METHODS: The study was conducted in two stages; the first stage was the translation and cultural/linguistic adaptation of the instrument; the second stage was the instrument's validation. RESULTS: The translated VitiQol showed high internal consistency (Cronbach alpha = 0.944) and high test-retest reliability and intraclass correlation coefficient=0.95 (CI 95% 0.86 - 0.98), p<0.001. There was no statistically significant difference between the means of the first completion of the VitiQoL questionnaire and the retest, p = 0.661. There was a significant correlation between VitiQoL and DLQI (r = 0.776, p <0.001) and also between VitiQoL-PB and subjects' assessment of the severity of their disease (r = 0.702, p <0.001). CONCLUSIONS: The impact of vitiligo on the QoL of Brazilian patients can be assessed by a specific questionnaire.